Pindars sechste olympische Siegesode : Text, Einleitung und Kommentar - Adorjáni, Zsolt. (Mnemosyne, Supplements, 2014)
Pindar's Sixth Olympian Ode is considered one of the poet's most brilliant victory odes. This is the first full-scale commentary on it. Adorjáni presents Greek text with critical apparatus, translation and metrical analysis. Three introductory chapters treat matters of history (background, date, performance) and literary criticism. Then follows a verse-by-verse commentary rooted in the tradition of philological exegesis, concentrating on grammatical, stylistic and interpretive features. Until now the Sixth Olympian has been praised chiefly for its magnificent and lucid presentation of the myth of Iamos, a seer of Arcadian origin and ancestor of the prophetic clan of the Iamidae. This commentary illuminates both the overwhelming depth of thought and the cunningly wrought structure of this masterpiece, contributing to a better understanding of Pindar's verbal artistry. Pindars sechste olympische Ode ist einer der glänzendsten Siegesgesänge des Dichters. Hier wird der erste umfassende philologische Kommentar zum Gedicht vorgelegt. Adorjáni bietet einen griechischen Text mit kritischem Apparat, Übersetzung, metrischer Analyse und drei Einleitungskapiteln, die in die Probleme der Geschichtlichkeit (Hintergrund, Entstehungszeit, Aufführung) und der literarischen Interpretation hineinführen. Auf diesen Teil folgt ein von Vers zu Vers fortschreitender Kommentar, der gemäß den alten Traditionen der Texterklärung auf grammatische, stilistische und interpretatorische Fragen eingeht. Bisher wurde Olympie 6 zumeist als großartige und suggestive Erzählung des Mythos des Sehers Iamos, des Vorfahren der olympischen Iamiden, gewürdigt. Diesem Kommentar ist daran gelegen, die intrikate Gedankentiefe und vollkommenste Formkunst dieses Meisterwerks vor Augen zu führen.